1977
DOI: 10.1136/jnnp.40.10.979
|View full text |Cite
|
Sign up to set email alerts
|

Increased myofibrillar protein catabolism in Duchenne muscular dystrophy measured by 3-methylhistidine excretion in the urine.

Abstract: SUM MARY Myofibrillar protein catabolic rate was calculated in seven patients with Duchenne muscular dystrophy from the amount of 3-methylhistidine excreted in the urine, and found to be over three times that found in a control series when expressed as the percentage (Ionasescu, 1975) have demonstrated abnormalities of protein synthesis in Duchenne muscular dystrophy, with high rates of synthesis of collagen, and low rates of non-collagen protein synthesis in the polyribosomes isolated from patients' muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 12 publications
3
16
1
Order By: Relevance
“…These higher rates of MHC synthesis are consistent with the previously reported high turnover rate of myofibrillar proteins (assessed by 3-methylhistidine and creatinine excretion) in DMD (4,35,36), mixed-muscle proteins in the mdx mouse (32), and the FSR of mixed-muscle protein in DMD and Becker dystrophy (42). We furthermore showed a clear rise in MHC synthesis in these subjects in response to oxandrolone.…”
Section: Discussionsupporting
confidence: 79%
“…These higher rates of MHC synthesis are consistent with the previously reported high turnover rate of myofibrillar proteins (assessed by 3-methylhistidine and creatinine excretion) in DMD (4,35,36), mixed-muscle proteins in the mdx mouse (32), and the FSR of mixed-muscle protein in DMD and Becker dystrophy (42). We furthermore showed a clear rise in MHC synthesis in these subjects in response to oxandrolone.…”
Section: Discussionsupporting
confidence: 79%
“…Previous investigations on muscle tissue from DMD patients (11)(12)(13)(14)(15)(16)(17) have reported increases in lysosomal protease activity, whereas the results reported here show that total acid autoproteolysis as well as a number of specific lysosomal enzymes are unchanged in DMD fibroblasts. Indeed, one report (13) has shown, contrary to our results on DMD fibroblasts, that DAP-I activity is increased in DMD muscle.…”
Section: Discussioncontrasting
confidence: 56%
“…A major obstacle in biochemical studies of dystrophic muscle has been the extensive secondary changes that occur in the degenerating skeletal muscle which serve to obscure the primary error of metabolism. Thus, there are reports of alterations in the levels of DMD skeletal muscle lipids (2,3), adenylate cyclase activity (4)(5)(6), activity of the sarcotubular system (7), protein synthesis (8), plasma membrane structure (9,10) and the activity of several lysosomal proteases (11)(12)(13)(14)(15)(16)(17). The fact that nonmuscle tissues are also affected clinically, although less critically, has suggested that the primary error might also be expressed in other organ systems (1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the available evidence indicates that the rapid loss of muscle protein and skeletal muscle mass that occurs during various muscle pathologies, such as the muscular dystrophies (McKeran et al, 1977;Ballard et al, 1979;Li, 1980;Warnes et al, 1981;Yoshikawa and Masaki, 1981), myasthenia gravis (Warnes et al, 1981), denervation (Goldberg, 1969b), phorbol diester treatment (West and Holtzer, 1982), and blockage of muscle membrane Na + channels (Crisona and Strohman, 1983), is due primarily to a greatly increased rate of muscle protein degradation with little change or even a slight increase in rate of muscle protein synthesis.…”
Section: Chaptermentioning
confidence: 98%